The application of the tsukamoto fuzzy method in controlling the dryer for shrimp cracker hygienization - Tyas, Kusumaningtyas; Ubaidillah Ms, Achmad; Rahmawati, Diana (SHM Publisher, 2023)
The process of drying crackers is traditionally carried out on the side of the road and open places. The impact of drying on product quality, especially hygiene because it is directly contaminated with dust, pollutants and pathogenic microbes. Drying depends on the sun's heat which affects the continuity of production and the level of drought. How to identify food hygiene using an inductive proximity sensor functions as a metal content detector. Because the metal content when ingested by humans is very dangerous. Drying is affected by temperature, moisture content and capacity. Oven drying application is equipped with an inductive proximity sensor and a DS18B20 temperature sensor. The Fuzzy Tsukamoto method for weight problems is grouped into a separate set. So that it can process oven temperature data. The control system for drying 3 shelves of crackers totaling 250 takes 25.6 minutes, drying 5 shelves of crackers totaling 410 takes 31.6 minutes. The drying process temperature is 30OC-70OC, the temperature used is a minimum of 60OC and a maximum of 65OC. Drying near the maximum temperature experiences a slowdown. If drying is done traditionally with the help of sunlight it takes longer.